2014
DOI: 10.1088/0004-6256/147/2/37
|View full text |Cite
|
Sign up to set email alerts
|

THE TYPE IIb SUPERNOVA 2013df AND ITS COOL SUPERGIANT PROGENITOR

Abstract: We have obtained early-time photometry and spectroscopy of supernova (SN) 2013df in NGC 4414. The SN is clearly of Type IIb, with notable similarities to SN 1993J. From its luminosity at secondary maximum light, it appears that less 56 Ni ( 0.06 M ) was synthesized in the SN 2013df explosion than was the case for the SNe IIb 1993J, 2008ax, and 2011dh. Based on a comparison of the light curves, the SN 2013df progenitor must have been more extended in radius prior to explosion than the progenitor of SN 1993J. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
94
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 77 publications
16
94
0
1
Order By: Relevance
“…We first present earlytime data on the SN itself and compare its properties to those of other well-studied SNe Ic, in particular SN 2007gr. We then show our detection of a candidate for the progenitor in archival Hubble Space Telescope (HST) images, which we isolated with high spatial resolution HST images of the SN; we initially reported this identification in Van Dyk et al (2017). Finally, we attempt to constrain the nature of the detected progenitor and compare these properties to predictions from the recent models of SESN progenitors.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…We first present earlytime data on the SN itself and compare its properties to those of other well-studied SNe Ic, in particular SN 2007gr. We then show our detection of a candidate for the progenitor in archival Hubble Space Telescope (HST) images, which we isolated with high spatial resolution HST images of the SN; we initially reported this identification in Van Dyk et al (2017). Finally, we attempt to constrain the nature of the detected progenitor and compare these properties to predictions from the recent models of SESN progenitors.…”
Section: Introductionmentioning
confidence: 90%
“…The situation is less clear for SNe whose progenitor has had its H-rich envelope partially or entirely stripped away before explosion, the so-called strippedenvelope SNe (SESNe; e.g., Filippenko 1997). We now have accumulating evidence that the progenitors of Type IIb SNe (SNe IIb), stripped but still retaining 0.1 M e of hydrogen, appear to be yellow to somewhat blue supergiants (e.g., Maund et al 2011;van Dyk et al 2011van Dyk et al , 2014Folatelli et al 2015;Bersten et al 2018), likely in interacting binary systems of moderate mass (∼12-15 M e ; e.g., Podsiadlowski et al 1993;Stancliffe & Eldridge 2009;Benvenuto et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The first spectrum, obtained by Cenko et al (2013), showed clear resemblance to the early spectra of SN 1993J, which suggested that SN 2013df was a SN IIb. This suspicion was verified by Van Dyk et al (2014) (hereafter VD14), who presented early photometric and spectroscopic data and reached conclusions concerning the properties of the progenitor, identifying it as a yellow supergiant star with an estimated initial mass of Min ∼13-17 M⊙, an effective temperature of T eff ∼4250 K, and an initial radius of R eff ∼545 R⊙. Morales-Garoffolo et al (2014) (hereafter MG14) presented a detailed analysis of early UV-optical light curves and some spectra, including nebular ones.…”
Section: Introductionmentioning
confidence: 84%
“…The quasibolometric light curve was derived by integrating the dered- . d Calculated in this work, adopted parameters: t 0 = 2,456,447.8 ± 0.5, E(B − V ) = 0.09 ± 0.01 mag, µ 0 = 31.10 ± 0.05 mag (Freedman et al 2001;Van Dyk et al 2014).…”
Section: Analysis Of the Early Bolometric Light Curvementioning
confidence: 99%
“…Prior to 2009, fourteen CCSN progenitor stars or progenitor outbursts (eight SNe II-P, three IIb, one IIn, one Ibn, and one II-pec) had been detected in pre-explosion images (Smartt 2009, and references therein). Over the last few years, at least six more (IIn: 1961V, 2009ip, 2010jl;IIb: 2011dh, 2013df; IIn-P: 2011ht) have been found (Smith et al 2010a(Smith et al , 2011aKochanek et al 2011;Foley et al 2011;Maund et al 2011;Van Dyk et al 2014;Fraser et al 2013a). Detection of these progenitors is crucial for gaining a better understanding of the observed SN diversity.…”
Section: Introductionmentioning
confidence: 99%